İngilizce öğretmenlerinin yeterlik algılarındaki değişimleri öngören sosyo-demografik ve kurumsal etkenler - Yavuz, Şenay (My University, 2005)
The present study aims to assess the level of the efficacy perceptions of English as a Foreign Language (EFL) teachers working at public and private universities in Turkey and investigate the socio-demographic and institutional factors that predict variations in these perceptions. The following research questions are particularly addressed: 1. What is the level of the efficacy perceptions of EFL teachers working at public and private universities in Turkey? 2. What are the socio-demographic factors that predict variations in EFL teachers' efficacy perceptions? 3.What are the institutional factors that predict variations in EFL teachers' efficacy perceptions? Subjects of this study comprised 226 EFL teachers serving at the preparatory schools of 13 universities (4 public, 9 private) in İstanbul. Data were collected by means of a teacher background questionnaire developed by the researcher, the Ohio State Teacher Efficacy Scale (OSTES) developed by Tschannen-Moran and Hoy (2001) and School-Level Environment Questionnaire developed by Fisher and Fraser (1990). Findings revealed that EFL teachers working at the preparatory schools of universities in Istanbul viewed themselves as highly efficacious. Moreover, it was found out that these teachers displayed more efficacy for classroom management and instructional strategies such as adjusting the level of their classes according to their students and using a variety of assessment strategies than for motivating students and engaging them in the learning process. Furthermore, the number of professional activities teachers were involved in, average number of students in teachers' classes, working position, type of institution, and gender were identified as the socio-demographic factors that predicted variations in EFL teachers' efficacy in this study. Finally, the findings obtained in this study indicated that a cooperative and respectful student profile and encouragement of innovation at the university were the institutional factors that predicted variations in EFL teachers' efficacy. KISA

İngilizce Öğretmenlerinin Yeterlik Algılarındaki Değişimleri Öngören Sosyo-Demografik ve Kurumsal Etkenler Şenay Yavuz Bu çalışma Türkiye' deki devlet ve özel üniversitelerde görev yapan İngilizce öğretmenlerinin yeterlik algılarının düzeyini ölçmeyi ve bu algıları öngören sosyo-demografik ve kurumsal etkenleri araştırmayı amaçlamaktadır. Çalışma özellikle aşağıdaki soruları yanıtlamayı amaçlar: 1.Türkiye' deki devlet ve özel üniversitelerde görev yapan İngilizce öğretmenlerinin yeterlik algıları ne düzeydedir? 2.İngilizce öğretmenlerinin yeterlik algılarını öngören sosyo-demografik etkenler nelerdir? 3.İngilizce öğretmenlerinin yeterlik algılarını öngören kurumsal etkenler nelerdir? Bu çalışmanın deney grubu İstanbul'daki 13 (4 devlet, 9 vakıf) üniversitenin hazırlık bölümlerinde görev yapan 226 İngilizce öğretmeninden oluşmaktadır. Çalışma için gerekli olan veriler, araştırmacı tarafından hazırlanan bir öğretmen anketi, Tshannen-Moran ve Hoy (2001) tarafından geliştirilen Ohio Eyaleti Öğretmen Yeterlik Ölçeği ve Fisher ve Fraser (1990) tarafından geliştirilen Okul Düzeyi Çevre Anketi kullanılarak elde edilmiştir. Elde edilen bulgular, İstanbul'da ki üniversitelerin hazırlık bölümlerinde çalışan öğretmenlerin kendilerini oldukça yeterli gördüğünü göstermiştir. Bunun yanı sıra, bu öğretmenlerin sınıf yönetimi ve seviyeyi öğrenci grubuna göre ayarlama ve çeşitli ölçme stratejileri kullanma gibi ders anlatma ve ölçme-değerlendirme ile ilgili stratejilerde daha yüksek yeterlik gösterirken, öğrenciyi motive etme ve öğrenme sürecine dahil etme konusunda ayni yeterliği sergilemedikleri bulunmuştur. Bu bulgulara ek olarak, öğretmenlerin profesyonel gelişim için yaptıkları aktivitelerin sayısı, sınıflardaki öğrenci sayısı, öğretmenlerin görevleri, kurum türü, ve cinsiyet bu çalışmadaki İngilizce öğretmenlerinin yeterliğindeki değişimleri öngören sosyo-demografik etkenler olarak saptanmıştır. Son olarak, bu çalışmada elde edilen bulgular öğretmeni ile öğrenme sürencinde işbirliği yapan, saygılı bir öğrenci profilinin ve bir üniversitenin yeniliklere ne kadar açık olduğunun İngilizce öğretmenlerinin yeterliğindeki değişimleri öngören kurumsal etkenler olduğunu göstermiştir.
Keywords: Eğitim; Okul organizasyonu ve yönetimi; Öğretim ve öğretim kadrosu; Öğretmenler